2013
DOI: 10.1007/s12975-013-0272-3
|View full text |Cite
|
Sign up to set email alerts
|

Bipyridine, an Iron Chelator, Does Not Lessen Intracerebral Iron-Induced Damage or Improve Outcome After Intracerebral Hemorrhagic Stroke in Rats

Abstract: Iron chelators, such as the intracellular ferrous chelator 2,2'-bipyridine, are a potential means of ameliorating iron-induced injury after intracerebral hemorrhage (ICH). We evaluated bipyridine against the collagenase and whole-blood ICH models and a simplified model of iron-induced damage involving a striatal injection of FeCl2 in adult rats. First, we assessed whether bipyridine (25 mg/kg beginning 12 h post-ICH and every 12 h for 3 days) would attenuate non-heme iron levels in the brain and lessen behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Therefore, those studies suggest that there are critical differences between these ICH models. Additionally, bipyridine, an iron-chelator, does not lessen intracerebral iron-induced damage or improve outcome after ICH in rats [ 170 ]. Perhaps, the current clinical work with iron-chelator will help identify the more clinically predictive model for future neuroprotection studies [ 171 ].…”
Section: Antioxidant Therapy After Ichmentioning
confidence: 99%
“…Therefore, those studies suggest that there are critical differences between these ICH models. Additionally, bipyridine, an iron-chelator, does not lessen intracerebral iron-induced damage or improve outcome after ICH in rats [ 170 ]. Perhaps, the current clinical work with iron-chelator will help identify the more clinically predictive model for future neuroprotection studies [ 171 ].…”
Section: Antioxidant Therapy After Ichmentioning
confidence: 99%
“…Clioquinol, a ferrous iron chelator, improved the neurological outcome and attenuated brain oedema and ROS production besides reducing iron levels . Another ferrous chelator, 2,2′‐bipyridine, is a potential means of ameliorating iron‐induced injury after ICH ; unfortunately, another results failed to support the use of bipyridine against ICH , and the function of bipyridine on ICH is uncertain so far.…”
Section: The Agonists For the Other Scavenger Receptorsmentioning
confidence: 99%
“…Furthermore, this study found that DP post-treatment ameliorated neurobehavioral deficits and brain oedema formation while not affecting mortality rates. However, more recently, Caliaperumal et al 217 performed a series of experiments assessing DP's effect following ICH and found that it failed to chelate non-haem iron levels following ICH, failed to reduce oedema in the ipsilateral cortex and failed to lessen tissue loss or decrease neurodegeneration. These somewhat contradictory findings could be partly explained by the difference in experimental setup (the first was more focused on a pretreatment vs post-treatment administration while the second was simply assessing post-treatment in a variety of circumstances), but they still warrant further investigation and clarification.…”
Section: Treatmentsmentioning
confidence: 99%